PEMENUHAN HAK-HAK KAUM DIFABEL DALAM KERANGKA HAK AZASI MANUSIA - Fajar Fajar (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
AbstractThis study describes the rights of persons with disabilities in the eyes of human rights. Nowadays, the disabled are positioned as second-class people whose rights are often neglected, both from the aspect of policy as well as state development. The state and society as a totality of structures are ignorant in presenting a space that accommodates the rights of people with disabilities based on diversity of every human ability. Therefore, the problems of people with disabilities can be resolved by the approach of social welfare or compassion as a result of the failure of the state to see the core issuesof the diffable holistically. Therefore, in the future there should be a special institution in the form of the Commission for the Protection of the Rights of People with Disabilities (KPHD) to resolve the complexity of disability issues in terms of social, cultural, educational, legal, and political aspects.Keywords: Fulfilment of rights, diffable, Human Rights.AbstrakKajian ini menjelaskan tentang hak-hak kaum difabel atau disabilitas dalam kacamata Hak Azasi Manusia (HAM). Dimana selama ini kaum difabel diposisikan sebagai masyarakat kelas dua yang seringkali terabaikan hak-haknya, baik dari aspek kebijakan maupun dari aspek pembangunan negara.Negara dan masyarakat sebagai satu totalitas struktur abai dalam menghadirkan suatu ruang yang mengakomodir hak-hak kaum difabel yang didasarkan pada keragaman kemampuan setiap manusia atau difabilitas. Sehingga permasalahan kaum difabel seringkali diselasaikan dengan pendekatan kesejahteraan sosial atau belas kasih sebagai akibat dari kegagalan negara melihat inti permasalahan difabel secara holistik. Oleh karena itu, kedepannya semestinya ada lembaga khusus berupa Komisi Perlidungan Hak-hak Kaum Difabel (KPHD) untuk menyeselaikan kompleksitas permasalahan difabel baik dari sisi sosial, budaya, pendidikan, hukum, maupun politik.Kata kunci: Pemenuhan hak, Difabel, HAM.